Teacher-learner interactions in Indonesian EFL classroom: A case study of active learning strategies and proficiency challenges - Huda, Bahrul; Yunus, Muhammad; Romadhon, M. Galuh Elga (Journal on English as a Foreign Language, 2025)
Second language acquisition (SLA) research often prioritizes adult and tertiary-level learners, leaving adolescent learners in secondary schools underrepresented. This study investigates how teacher–learner interactions shape SLA in Indonesian junior high school classrooms, focusing on instructional strategies and contextual challenges. Using a qualitative case study design, data were collected through classroom observations and semi-structured interviews with four teachers and thirty-two students. Thematic analysis revealed that scaffolding, modified input, peer collaboration, and implicit feedback were key strategies that fostered engagement, comprehension, and learner confidence. Teachers employed stepwise guidance, slowed speech, visual supports, and role-plays to encourage active participation, while rephrased feedback helped reduce anxiety during error correction. However, persistent challenges emerged, including student anxiety, wide proficiency gaps, limited teaching resources, and overcrowded classrooms, which constrained interaction patterns. The findings highlight the importance of differentiated instruction, low-anxiety learning environments, and resource support to optimize SLA in adolescent EFL contexts. This study contributes to SLA literature by emphasizing the critical role of interactive strategies in promoting effective language acquisition among younger learners in non-western settings.